SPATIAL-TEMPORAL ANALYSIS OF FISHING BOAT MOVEMENTS BASED ON AIS IN THE INDONESIAN FISHERIES MANAGEMENT AREA (WPPNRI) 573: ANALISIS SPASIAL TEMPORAL PERGERAKAN KAPAL PERIKANAN BERBASIS AIS DI WPPNRI 573 - Fathurrahman Arizqi; Denianto Yoga Sativa; Lalu Samsul Rizal; Hamid Hamid (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The movement patterns of fishing boats in the Indonesian Fisheries Management Area (WPPNRI) 573, particularly in the Indian Ocean, the Lombok Strait, and the Bali Strait, have not been recorded spatially and temporally. This study aims to monitor, analyze, and compare the spatial-temporal patterns of fishing boat movements, as observed over 6 months, based on AIS (Automatic Identification System) data in the GFW (Global Fishing Watch) geoportal. Remote sensing methods apply spatial-temporal analysis to the movement vectors of fishing boats and graph the fluctuations in the number of fishing ground points. AIS monitors boat movements based on broadcasting system transponders operated via Very High Frequency (VHF) radio waves, namely between 156 and 162 MHz. The results of monitoring AIS GFW data from January to June show a pattern of boat movements from the Bali Strait to the Indian Ocean. The density level of the boats in fishing operations is evenly distributed but concentrated in three fishing locations containing values ​​(suitability of environmental parameters) of chlorophyll-a (mg/m3), sea surface temperature-SST (°C), and salinity (psu), respectively, at 10°22’14.40” S/115°18’48.62” E (0.21, 29.5, 33.95); 12°58’40.58” S/119°10’47.99” E (0.12, 29.86, 34.71), and 12°45’56.08” S/117°46’20.03” E (0.11, 29.87, 34.66). The GFW Geoportal can detect, identify, compare, and analyze boat movements (including data filtration, boat grouping, downloading movement data, and fishing points) as well as environmental parameters. The movement patterns of fishing boats in this study were influenced by increased chlorophyll a and low SST, which resulted in increased fishing activity between April and June.